Physicochemical Parameters and Fish Catches of Zobe Reservoir in Katsina State, Nigeria - Nababa, Abdulsalam; Yusuf, Zikrulla A.; Umaru, Joel (Sahel Journal of Life Sciences FUDMA, 2024)
This study aimed to examine the physicochemical characteristics and fish catches of the Zobe reservoir. The study was carried out for a period of 12 months at five fishing stations (Tabobi, Makera, Garhi, Gada, and Raddawa). Standard techniques were employed to determine the physicochemical parameters of the reservoir. The ranges of values obtained were: temperature (22.00±2.2.54 – 32.00±.2.2.54°C); pH (5.90±0.50 – 9.00±0.50); Turbidity (4.5±0.84 - 8.00±0.84); Dissolved Oxygen (6.00±0.50 mgL-1 – 8.50±0.50 mgL-1); Biological Oxygen Demand (0.50 ± 0.54 mgL-1 – 3.80±0.07 mgL-1; Electrical Conductivity (EC): 65.00±13.23μS/cm – 199.00±13.227μS/cm; Alkalinity: 20.10 ±3.507 – 33.00 ±2.28ppm); Ammonia (0.10ppm ±0.20 – 0.50ppm±0.08ppm). Catches of fishers comprised thirteen (13) fish species from seven (7) families. O. niloticus of the Cichlidae family had the highest Catch per Unit Effort (CPUE) (22.28 and 9.93) for the dry season, whereas C. gariepinus had the highest CPUE in the wet season (22.22 and 9.80). Furthermore, C. anguilaris has the lowest CPUE, which is (0.08) in Makera in the dry season and (0.04) in Raddawa at the rainy season. Turbidity and fish catches had a negative correlation (-0.98), while EC and fish catch had a strong positive correlation (0.60). Physicochemical properties fall within permissible ranges for fish production. In conclusion, Zobe reservoir has enormous potential for fish production which could said to be not optimally utilized. Sustainable research is recommended to maximize the utilization of the fishery resources of the reservoir.